Measuring Collaboration Load With Pupillary Responses - Implications for the Design of Instructions in Task-Oriented HRI - Kontogiorgos, Dimosthenis; Gustafson, Joakim (Frontiers in Psychology, 2021)
In face-to-face interaction, speakers establish common ground incrementally, the mutual belief of understanding. Instead of constructing ‘one shot’ complete utterances, speakers tend to package pieces of information in fragments (what Clark calls ‘installments’). In this study, we investigated how speakers’ fragmented utterances affect the cognitive load of the conversational partners during utterance construction and comprehension. Pupillometry data and multimodal analyses indicated that more cognitive resources are required by speakers to construct fragmented rather than complete utterances, particularly in states of uncertainty. We also found that the construction of utterances by audience design indicated higher cognitive load for speakers, as adapting to listeners is a demanding task. We used pupil diameter as an online marker of cognitive processing in utterance construction, further demonstrating its usefulness as a measure of language production and comprehension. We discuss the results and their implications to the design of task-oriented human-robot interactions, and how guided-task social robots may benefit from the production of fragmented instructions.